Research in accounting: the case of Portuguese polytechnic higher education - Quesado, Patrícia (2021)
Purpose - This study aims to analyse the academic research in accounting, conducted in Portugal in recent years. The main goal is to identify past trends and future research opportunities. The focus is on Portuguese polytechnic higher education because is where are most accounting graduations and post-graduations. Design/methodology/approach - Based on bibliometric techniques, the study was carried out through the collection of information on master’s dissertations and applied research projects. The data was collected in the repositories of public polytechnic higher education institutions in Portugal that offer master’s degrees, in accounting and management. Findings - Applied research projects are few compared with dissertations. The major research approach is qualitative and most of the studies used document or content analysis. Most of the studies used the traditional research methods, in detriment of the innovative ones, as experimental studies. Financial accounting is the main area of investigation for the private and non-profit sector, but cost and management accounting is the main area for the public sector. Originality/value - The relevance of this research is to outline a general profile of scientific research on accounting, providing historical and statistical data for the strengthening of the studies in this field of knowledg